2010
DOI: 10.1007/s00253-010-2805-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of bacterial adhesion

Abstract: Management of bacterial infections is becoming increasingly difficult due to the emergence and increasing prevalence of bacterial pathogens that are resistant to available antibiotics. Conventional antibiotics generally kill bacteria by interfering with vital cellular functions, an approach that imposes selection pressure for resistant bacteria. New approaches are urgently needed. Targeting bacterial virulence functions directly is an attractive alternative. An obvious target is bacterial adhesion. Bacterial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 88 publications
1
77
0
3
Order By: Relevance
“…5 Anti-virulence methods target key stages in infection for preventing microbial attachment. Indeed, the monosuch as the adhesion of the pathogen to the host 6,7 or the sigdispersity of dendrimers is a key advantage when interpreting 16 nalling networks that coordinate the expression of virulence affinity data in term of size and multivalency. However, adfactors.…”
Section: Introductionmentioning
confidence: 99%
“…5 Anti-virulence methods target key stages in infection for preventing microbial attachment. Indeed, the monosuch as the adhesion of the pathogen to the host 6,7 or the sigdispersity of dendrimers is a key advantage when interpreting 16 nalling networks that coordinate the expression of virulence affinity data in term of size and multivalency. However, adfactors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that polymer-induced aggregation led to predictable changes in QS for a variety of cell types [17], and that QS signal activation and cell binding by polymers can lead to feedback in the QS pathways. Nevertheless, there are many complex interactions between bacterial cell signals, host cells [18], biofilm formation [14,[19][20][21] and polymeric materials which remain to be clarified in order to design appropriate materials to combat or to prevent bacterial infections. A number of polymeric materials with the ability to bind bacteria and/or QS signals have now been demonstrated [1,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…More precise understanding of the host-bacteria interactions will pave the way for the development of an effective drug. In this way, targeting bacterial colonization through blockade of selective adhesins could be therapeutically useful (Ofek et al, 2003;Klemm et al, 2010). There are a number of examples where inactivation of FnBP genes or antibodies to FnBPs has resulted in decreased bacterial colonization/virulence (Rennermalm et al, 2001;Rivas et al, 2004).…”
Section: Adhesins As Therapeutic Targetsmentioning
confidence: 99%